Predictors of sickness absence in pregnancy: a Danish cohort study - Hansen, Mette Lausten; Thulstrup, Ane Marie; Juhl, Mette; Kristensen, Jette Kolding; Ramlau-Hansen, Cecilia H. (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVE ': 'The aim of this cohort study was to investigate associations between parity, pre-pregnancy body mass index (BMI), assisted reproductive therapy (ART), time to pregnancy (TTP), and engagement in physical exercise and the risk of sickness absence in pregnancy from 10–29 completed pregnancy weeks. ' ' METHODS ': 'Data from 51 874 pregnancies in the Danish National Birth Cohort collected from 1996 until 2002 were linked to the Danish Register for Evaluation of Marginalization. Exposure information was based on questionnaires. Hazard ratios (HR) with 95% confidence intervals (95% CI) were calculated by Cox regression, using time of first episode of sickness absence as the primary outcome. ' ' RESULTS ': 'Multiparity 1.26 (95% CI 1.10–1.45), overweight 1.13 (95% CI 1.08–1.18), obesity 1.23 (95% CI 1.15–1.31), ART 1.10 (95% CI 1.01–1.20), and TTP >12 months 1.06 (95% CI 0.99–1.13) were associated with higher HR of sickness absence. Physical exercise of >120 minutes per week was associated with lower HR 0.84 (95% CI 0.75–0.95). ' ' CONCLUSION ': 'Risk for sickness absence was higher among women who were multiparous, overweight, obese, received ART, and had prolonged TTP, and lower among women engaged in leisure-time physical exercise. Few studies have investigated these associations, and the results should be confirmed in other studies of pregnant women.
Keywords: assisted reproductive therapy; body mass index; cohort study; Danish National Birth Cohort; Denmark; parity; physical exercise; predictor; pregnancy; sickness absence; time to pregnancy